The Effect Of Using Multimedia Macromedia Flash On Student Mathematics Communication At SMP Negeri 1 Labuhan Deli - Fitri Adhiningsih Rizky; Izwita Dewi (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This research is a quasi-experimental research. The research conducted at SMP Negeri 1 Labuhan Deli aims to find out. 1) To find out how the mathematical communication ability of students who learn to use Macromedia Flash. 2) To find out how the mathematical communication ability of students who learn without using Macromedia Flash. 3) To find out whether the mathematical communication of students who learn using Macromedia Flash media is better than the mathematical communication of students who learn without using Macromedia Flash media for class VII students at SMP Negeri 1 Labuhan Deli T.A. 2021/2022. The population in this study were all students of class VII at SMP Negeri 1 Labuhan Deli. Using a homogeneous technique, samples were taken from 2 classes of population. One class was used as the experimental class, namely class VII-2 which was taught with Macromedia Flash and class VII-3 which was used as the control class, namely class which was taught without using Macromedia Flash. As a data collection tool using PreTest and PostTest. In this study 1) the mathematical communication ability of students learning to use Macromedia Flash with an average pretest of 67.77 and a posttest of 85.54. 2) the mathematical communication ability of students who learn without using Macromedia Flash with an average pretest of 67.13 and a posttest of 77.54. then testing the hypothesis for learning outcomes using paired t-test. after testing the data, it turns out that the results of testing the ability of learning outcomes in the experimental class at the pretest level α = 0.05 with Lcount < Ltable, namely 0.09452 <0.192 and posttest 0.1228 <0.192 , and the results of testing the ability of learning outcomes in the control class at the pretest level α = 0.05 with Lcount < Ltable, namely 0.1014 < 0.184 and posttest 0.1659 < 0.184, then H0 is accepted and Hi is rejected. Thus it can be concluded that the mathematical communication ability of students who use macromedia flash media are better than those without using macromedia flash media.